Some Normative and Institutional Developments in the Field of Common Agricultural Policy and their Consequences on the Protection of the European Citizens’ Interests - Gabriela Alexandra Oanţă (Romanian Journal of European Affairs)
This paper intends to briefly comment on some changes in the field of Common Agricultural Policy, especially regarding the safety of agricultural products and foodstuff. Within the framework of the CAP the food safety has managed to progressively constitute its third pillar, currently boasting an outstanding place in the attainment of its objectives. CAP has been progressing in its mechanisms and legal instruments towards a more relevant integration of the concerns relative to the consumer’s health protection and to the food safety in the objectives to be reached.